Respons Indonesia terhadap Kasus Penyadapan Australia - Shaffan, Ahmad Mafud; Wahyudi, Fendy Eko; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
In 2013, widespread preaching on wiretapping scandal conducted by the United States and its allies. This news comes after a leak of data about the list of people who tapped included their nationality. Edward Snowden, a former NSA contractor who spread the secret data. Australia was mentioned in the news by wiretapping several key people in Indonesia, including President Susilo Bambang Yudhoyono. In response, the Government of Indonesia took some action as a clarification step by withdrawing the Ambassador, also cutting all bilateral aggrement in security and information sector. This study will aim to examine the causes of the Government of Indonesia in issuing such responses. Using the concept of national security based on the actor's understanding of threats coming measured by its own vulnerabilities. This research proves that the reason the Government of Indonesia in doing the response is based on the existence of national insecurity caused by wiretapping’s threats that are been there cause of vulnerabilty of Indonesian’s technology and information security